Production of hydrogen and lithium hydroxide in alkaline environments

By using the LiSICon film electrochemical battery in an alkaline medium for membrane electrolysis and electrochemical decomposition of water, the problem of low lithium recovery efficiency in waste lithium ion battery packs is solved, and high purity lithium recycling and high energy efficiency production are achieved.

CN119855790APending Publication Date: 2025-04-18EVONIK OPERATIONS GMBH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380065202.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-12
Filing Date
2023-09-01
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently recover lithium from waste lithium-ion battery packs, and traditional methods are sensitive to impurities, resulting in short film life and low energy efficiency.

Method used

The membrane electrolysis of electrochemical cells is carried out in an alkaline medium, and combined with the electrochemical decomposition of water, selective separation of lithium and production of lithium hydroxide are achieved. This method ensures long life and efficient energy utilization of the membrane by adjusting the pH of the feed and using high current density.

Benefits of technology

Efficient lithium recovery is achieved, the purity of lithium meets the standards of battery production, and can still maintain the long life and high energy efficiency of the film when impurities are present.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119855790A_ABST
    Figure CN119855790A_ABST
Patent Text Reader

Abstract

The invention relates to the electrochemical production of hydrogen and lithium hydroxide from Li + containing water using LiSICon membranes. The problem addressed by the invention is that of proposing a method which can be operated economically even on an industrial scale. The process will exhibit higher energy efficiency and achieve a long service life of the membrane even if the feedstock used contains impurities that are detrimental to the LiSICon material. The method is characterized in that the battery separates lithium through a membrane and electrolyzes water at the same time. One important aspect of the method is that the electrochemical method is carried out in an alkaline environment, more accurately, the pH value is 9 to 13. The pH is adjusted by adding a basic compound to the feed.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] For the production of lithium-ion batteries (LIBs), lithium (Li) is by definition necessary. Due to its high reactivity, lithium does not exist in pure form in nature, but always in bound form. The starting material for the production of LIBs is generally lithium in the form of lithium hydroxide (LiOH) or lithium carbonate (Li2CO3).

[0002] In most natural deposits, Li is present in the form of lithium oxide (Li2O) or salts such as lithium sulfate (Li2SO4) or lithium chloride (LiCl). Lithium oxide is a component of ores such as pegmatites, while lithium sulfate and lithium chloride are present in dissolved form in the leachate of Li salt lakes. During the mining process, the extracted lithium compounds are converted into lithium carbonate (Li2CO3) in certain cases. In a further process step, lithium carbonate can be converted into lithium hydroxide by reaction with quicklime or calcium hydroxide. The extraction of Li and its conversion into LiOH are described in:

[0003] Wietelmann, U. and Steinbild, M. (2014). Lithium and Lithium Compounds. In Ullmann's Encyclopedia of Industrial Chemistry, (ed.). DOI: 10.1002 / 14356007.a15_393.pub2.

[0004] Rich Li deposits are well known, but the production of LiOH from the Li compounds they contain is very energy intensive and produces large amounts of wastewater. There is also a strategic need to break away from dependence on the owners of the deposits.

[0005] One solution to this problem may be to reprocess the material from spent LIBs so that the lithium contained therein can be reused as a raw material for new batteries.

[0006] Recovery methods for LIBs have been developed to industrial maturity in the past, but in most cases for the metals Fe, Ni, Mn, Co, Mg and Al present therein. Alkali metal Li is generally not recovered because its high reactivity makes it difficult to separate from spent batteries and it is available in sufficient quantities from natural deposits at low cost. For a long time, the extraction of Li from spent LIBs seemed simply uneconomical.

[0007] However, there is now increasing social and economic pressure to recover lithium from used LIBs. In order to realize this idea, it is necessary to supply LIB producers with recycled Li in an acceptable quality so that the method for making LIBs from recycled Li is no different from the method for making LIBs using mined virgin Li. It goes without saying that there must be no adverse effect on the quality of the battery pack. Therefore, the recovered Li, especially the recovered Li in the form of LiOH, must meet very strict specifications on purity. In addition, the method for recovering Li from old batteries must be as energy efficient as possible. The method should also use very little water.

[0008] Known methods for recovering lithium from old batteries are summarized in the following document:

[0009] Pankaj K.Choubey et al.:Advance review on the exploitation of the prominent energy-storage element Lithium.Part II:From sea water and spentlithium ion batteries(LIBs),Minerals Engineering,volume 110,2017,pages 104-121

[0010] DOI:10.1016 / j.mineng.2017.04.008.

[0011] The "LISM" technology, which is mentioned only in passing in the above-mentioned review article, is the electrolysis of Li-containing water in the presence of so-called LiSICon membranes.

[0012] LiSICon stands for lithium superionic conductor. This is a class of inorganic glass-ceramic materials that are electrical insulators but at the same time have intrinsic conductivity for Li ions. The transport mechanism of Li derives from the crystal structure of the material. In short, the Li ions "pass through" the crystal. Commercially available LiSICon materials include lithium aluminum titanium phosphate (LATP), lithium aluminum silicon titanium phosphate (LATSP), lithium aluminum germanium phosphate (LAGP) and lithium lanthanum titanium oxide (LLTO). These materials were originally developed as solid-state electrolytes for LIBs. An overview of the transport mechanism of LiSICon, their crystal structure and manufacture is given in the following literature:

[0013] Palakkathodi Kammampata et al.:Cruising in ceramics–discovering new structures for all-solid-state batteries–fundamentals,materials,andperformances.Ionics 24,639-660(2018)DOI:10.1007 / s11581-017-2372-7

[0014] Yedukondalu Meesala et al.:Recent Advances in Li-Ion Conductorsfor All-Solid-State Li-Ion Batteries.ACS Energy Lett.2017,2,12,2734-2751DOI:10.1021 / acsenergylett.7b00849

[0015] Feel free to use the LiSICon kit:

[0016] Sophia Saffirio et al 1.4 Al 0.4 Ge 0.4 The 1.4 (PO4)3promising NASICON-structured glass-ceramic electrolyte for all-solid-state Li-based batteries:Unravelling the effect of diboron trioxide,Journal of the European CeramicSociety,volume 42,issue 3,2022,pages 1023-1032DOI doi: 10.1016 / j.jeurceramsoc.2021.11.014.

[0017] Eongyu Yi et al.Materials that can replace liquid electrolytes in batteries:Superionic conductivities in Li 1.7 Al 0.3 The 1.7 Si0.4 P 2.6 O 12 .Processingcombustion synthesized nanopowders to free standing thin films. Journal of Power Sources, volume 269, 2014, pages 577-588, DOI 10.1016 / j.jpowsour.2014.07.029.

[0018] The selective conduction of Li ions by LiSICon materials means that LiSICon materials can be used as membranes for separating Li from Li-containing mixtures. The Li must be present in the mixture in ionic form, for example as a Li salt dissolved in water. The driving force required to push the Li ions through the LiSICon membrane is voltage. For this purpose, an electrochemical cell is constructed, which includes two electrodes and a LiSICon membrane that divides the cell into two compartments. In each compartment, there is an electrode. The compartment is called negative or positive, depending on the polarity of the electrode present in each compartment. A voltage is applied to the electrodes and the anion compartment is filled with Li-containing water. The positive compartment is filled with water. The membrane allows Li cations to pass through to the positive electrode. As a result, the water in the positive compartment becomes rich in Li, while the water on the negative side becomes deficient in Li. Such a method is called membrane electrolysis.

[0019] Membrane electrolysis processes for extracting lithium by means of LiSICon membranes have been described in the prior art.

[0020] For example, Zhen Li et al. describe a method using weakly lithium-bearing water from the Red Sea as a raw material:

[0021] Zhen Li et al.: Continuous electrical pumping membrane process for seawater lithium mining. Energy Environ. Sci., 2021, 14, 3152 DOI: 10.1039 / d1ee00354b.

[0022] Zhen Li's research group used LLTO as a membrane. The separated target product is lithium phosphate (Li3PO4), which is suitable for the production of lithium iron phosphate (LFP) battery packs. It cannot be directly used to manufacture LIBs with different cathode materials, such as nickel-manganese-cobalt (NMC) or lithium manganese oxide (NMO).

[0023] Yang et al. have managed to extract metallic lithium directly from seawater using solar energy, LAGP membrane and copper foil.

[0024] Sixie Yang et al.: Lithium Metal Extraction from Seawater. Joule, volume2, issue 9, 2018, pages 1648-1651, DOI 10.1016 / j.joule.2018.07.006.

[0025] US2016 / 0201163 A1 describes the separation of Li ions from salt water such as seawater by means of a LiSICon membrane. The membrane materials proposed are specifically Li3N, Li 10 GeP2S 12 ,La x Li y TiO2 and Li 1+x+y Al x (Ti,Ge) 2-x Si y P 3-y O 12 The target product is lithium carbonate (Li2CO3).

[0026] WO 2019055730 A1 is also about separating lithium by means of a LiSICon membrane. LLTO, LAGP and LATP are specifically mentioned. The LiSICon material can be applied to a support structure. The chemical properties of the support structure are not described in detail. Likewise, there is very little description of how to implement the application of LiSICon to the support structure. The target product separated is Li ions.

[0027] US Pat. No. 9,222,148 B2 also discloses the separation of lithium hydroxide by membrane electrolysis on a LiSICon membrane and subsequent precipitation of lithium hydroxide hydrate.

[0028] In addition to the use of ceramic LiSICon membranes, electrolytic processes for lithium separation using organic ion exchange membranes are also known.

[0029] For example, EP 3805428 A1 describes the electrolytic production of lithium hydroxide. In addition to the electrolysis, an electrochemical conversion of lithium into lithium hydroxide is also carried out. In order to obtain the necessary reactants, water undergoes a simultaneous electrochemical decomposition. This is done using a bipolar three-compartment cell with an ion exchange membrane. Commercially available AVV, 902, FAB, FKB and CMB ion exchange membranes. The chemical nature of these ion exchange membranes is not disclosed in EP 3805428 A1, but they will most likely be organic membrane materials. The three-compartment cell operates in an acidic medium. In particular, water containing a Li salt such as lithium sulfate (Li2SO4) or lithium chloride (LiCl) is used as feed.

[0030] US10036094 B2 discloses a two-stage electrodialysis / electrolysis production of lithium hydroxide from aqueous lithium sulfate and / or lithium hydrogen sulfate solutions with simultaneous water decomposition. The first stage employs an electrochemical cell with two compartments, and the second stage employs a three-compartment cell. The prevailing pH in the three-compartment cell may be 8 to 10. The cell is equipped with an ion exchange membrane. The chemical composition of the ion exchange membrane is not given. The following commercial membranes are mentioned: FAB, ACM, MV, 324 and AHA.

[0031] The main disadvantage of polymer membranes is their permeability to water. This results in dilution of the anolyte by water from the catholyte. In addition, organic ion exchange membranes have lower ion selectivity than inorganic LiSICon materials. They not only allow Li + By, and allow Na + In addition to the purity of the target product, the electrical efficiency of the process is also affected: if non-ion selective membranes are used for electrolysis, the unwanted Na + The transmission to the second compartment will also consume precious energy. In addition, when reaching the second compartment, Na + The membranes are not suitable for the conversion of Li into undesirable byproducts by unintended electrochemical processes. The energy efficiency of the process based on the yield of the target product Li is reduced. Finally, these membranes are not suitable for materials such as Mg 2+ and Ca 2+ Over time, these cations poison the membrane, thus limiting the useful life of organic ion exchange membranes.

[0032] Glass-ceramic LiSICon materials ensure better ion selectivity. However, the stability of LiSICon membranes towards impurities remains a highly significant issue for industrial practice. For example, Li-containing + Water contains other cations, especially such as Na + and K + , which causes lasting damage to the LiSICon material: These cations appear to occupy defects in the crystal structure, making the Li+ The transport of cations through the membrane almost stops. The service life of the electrochemical cell then expires. The high cost of LiSICon materials means that it is uneconomical to recover Li from LIBs if the service life of the membrane is short. In addition, the brine from Li salt lakes has a naturally high sodium content and is therefore not in contact with known LiSICon membranes. Therefore, lithium from salt lakes is additionally subjected to energy-intensive thermal separation and / or a stepwise process using large amounts of water in which lithium dissolves and then recrystallizes. Although the water here can be evaporated by solar radiation, water for dissolving LiCl is scarce in the deserts of South America. Therefore, this approach is extremely problematic there.

[0033] Another practical problem is the high specific resistance of the LiSICon material. This results in an electrochemical cell with a high ohmic internal resistance, which means that the process has a correspondingly high electrical energy requirement. In order to reduce this, the membrane could theoretically be made thinner. However, the low thickness of the material also results in only a short life in aggressive environments.

[0034] Based on all the above, the problem addressed by the present invention is to specify a method for obtaining a Li-containing + A process for the electrochemical production of LiOH in water which can also be operated economically on an industrial scale. In particular, the process should have good energy efficiency and achieve a high membrane life even when the feed used contains impurities which are harmful to the LiSICon material.

[0035] This problem is solved by a method according to claim 1 .

[0036] Therefore, the present invention first provides a method for producing hydrogen and lithium hydroxide, which comprises the following steps:

[0037] a) providing a feed comprising at least water, Li cations, anions and impurities, wherein the concentration of Li cations in the feed is C F at least 200 ppm by weight or between 500 ppm by weight and 140 000 ppm by weight, in each case based on the total weight of the feed, the pH of the feed being between 2 and 9, measured at 25° C. using a glass electrode;

[0038] b) providing a lean working medium comprising water and lithium hydroxide dissolved therein, wherein the concentration of lithium hydroxide in the lean working medium is C based on the total weight of the lean working medium. M0 At least 50 ppm by weight;

[0039] c) providing a basic compound;

[0040] d) providing at least one electrochemical cell, wherein the electrochemical cell has the following properties:

[0041] i. The electrochemical cell comprises a first compartment in which a negative electrode is arranged;

[0042] ii. The electrochemical cell comprises a second compartment in which a positive electrode is arranged;

[0043] iii. The electrochemical cell comprises a membrane separating the first membrane from the second membrane, the membrane having an area A;

[0044] iv. The membrane comprises an inorganic material having conductivity to Li ions and electrical insulation;

[0045] e) providing at least one voltage source connected to the negative electrode via a first electrical lead and to the positive electrode via a second electrical lead;

[0046] f) metering the basic compound into the feed so that an intermediate is obtained, the pH of which, measured at 25° C. using a glass electrode, is between 9 and 13;

[0047] g) filling the first compartment with the intermediate;

[0048] h) filling the second compartment with the lean working medium;

[0049] i) charging the electrochemical cell with a voltage U drawn from the voltage source so that a current I flows between the negative electrode and the positive electrode, the ratio Q of the current intensity of the current I to the area A of the membrane being between 100 A / m 2 and 500A / m 2 Between or 150A / m 2 and 350A / m 2 between;

[0050] j) extracting wastewater containing at least water, Li salt dissolved therein, oxygen and impurities from the first compartment, wherein the concentration of Li ions in the wastewater is C based on the total weight of the wastewater. W Lower than the concentration of Li ions in the feed C F ;

[0051] k) extracting a rich working medium containing water, lithium hydroxide and hydrogen from the second compartment, wherein the concentration of lithium hydroxide in the rich working medium is C based on the total weight of the rich working medium. M1 Greater than the concentration C of lithium hydroxide in the lean working medium M0 .

[0052] A particular aspect of the method according to the invention is that the selective separation of lithium by the membrane and the electrolysis of water are carried out simultaneously in the cell. In the electrolysis of water, water (H2O) is electrochemically decomposed into H2 and O2. At the positive electrode, OH is formed. - and hydrogen. However, OH- Anions cannot pass through the LiSICon membrane and are unable to interact with the Li + The cations combine to form lithium hydroxide LiOH. At the negative electrode, oxygen and H + .

[0053] Simultaneous Li-ionization in an electrochemical cell with a LiSICon membrane + Membrane separation and water electrolysis thus lead to the direct formation of lithium hydroxide LiOH and molecular hydrogen H2. LiOH dissolves in water, and H2 also dissolves in water to a small extent, but mostly exits in gaseous form. Water containing LiOH and dissolved gaseous H2 is drawn out of the cathode compartment. LiOH is separated from water. This makes it possible to extract LiOH, which has a purity sufficient for battery production due to the selective migration of lithium ions through the membrane.

[0054] At the same time the escaping hydrogen can be collected and used in the hydrogen economy. If the electrochemical cell is operated with green electricity, the method also leaves a small CO2 footprint.

[0055] The feed required for the combination of Li separation and water electrolysis is Li + Cationic water. Such water is produced during the reprocessing of used LIBs or alternatively using Li brines from natural deposits.

[0056] A key aspect of the method according to the invention is that the electrochemical process is carried out in an alkaline medium, more precisely at a pH of 9 to 13. This allows efficient water electrolysis, which in turn is a prerequisite for the direct production of LiOH. In addition, preliminary long-term studies have shown that the LiSICon material has a particularly long lifetime in this pH range even at high current densities.

[0057] In both the first compartment and the second compartment, the prevailing pH is preferably between 9 and 13. The pH in the two cells may be the same or it may be different, as long as it is between 9 and 13 in both cases. This is because an examination of the half-cell reactions for water splitting shows that the combination of an anolyte cell operated with an acidic feed and a catholyte cell operated with an alkaline working medium requires a higher voltage for water splitting than the combination of two half-cells each with an alkaline feed. Therefore, an alkaline pH in both half-cells (compartments) is particularly advantageous because it requires a lower voltage for the same process. The energy savings obtained by reducing the voltage when an alkaline process is present in both compartments is in the range of about 5% to 15%, depending on the voltage level selected for the membrane process, compared to a process in which an acidic pH is present in the anolytic compartment and an alkaline pH prevails in the cathodic compartment.

[0058] Since lithium-containing material streams from battery recovery or seawater are usually not alkaline, but tend to be acidic (pH 4 to 9), the pH is adjusted according to the invention by adding alkaline compounds to the feed. Only the resulting intermediate with the desired pH of 9 to 13 is fed to the battery. The pH values ​​are specified for a temperature of 25°C. The pH is measured using a glass electrode calibrated with a commercially available test liquid.

[0059] According to the invention, the cathode compartment is filled with a working medium. This is water with a variable concentration of LiOH. In the inflow of the second compartment, the LiOH concentration c M0 is at least 50 ppm by weight. In the effluent, the LiOH concentration c M1 The inflow is therefore called "lean working medium" and the outflow is called "rich working medium". The properties "lean" and "rich" are related to the LiOH content. The lower limit c of the LiOH content in the lean working medium must be met. M0 >50 ppm, so that the process can be started with low resistance in the working medium: it has been found that when the second compartment is filled with water without LiOH, the desired production of LiOH and H2 proceeds less successfully. There is no specific upper limit for the LiOH concentration in the lean working medium. However, it must be the case that M0 <c M1 , since otherwise the process does not produce any LiOH. 50 wt ppm of LiOH is equivalent to 15 wt ppm of lithium.

[0060] Another key aspect of the process according to the invention is the high current density with which it operates. Specifically, the current density, i.e. the ratio Q of the current intensity of the current I to the area A of the membrane, is between 100 A / m 2 and 500A / m 2 Between, or preferably 150A / m 2 and 350A / m 2 These high current densities allow high electrical efficiency, but they also require the membrane material to show good stability under harsh conditions. Therefore, the membrane material selected is an inorganic material that is electrically insulating and at the same time conductive to Li ions. An example of a suitable membrane material is the glass ceramic LiSICon.

[0061] The alkaline compound used to adjust the pH of the intermediate is preferably one of the following substances or mixtures: calcium hydroxide (Ca(OH)2), potassium hydroxide (KOH), sodium hydroxide (NaOH), lithium hydroxide (LiOH) and ammonium hydroxide (NH4OH). These substances are preferably used in the form of aqueous solutions, in other words potassium hydroxide solution, sodium hydroxide solution, lithium hydroxide solution or ammonia solution. Such aqueous solutions are easy to meter in. Potassium hydroxide solution and sodium hydroxide solution are relatively inexpensive. The lithium hydroxide solution is preferably produced itself in the process.

[0062] Very particular preference is given to using Ca(OH)2 as the alkaline compound. Calcium hydroxide is used in particular in its hydrated form, i.e. as slaked lime. Slaked lime is readily available. The advantage of slaked lime over potassium hydroxide solution and sodium hydroxide solution is that it contains virtually no K or Na. This means that the intermediates are not oxidized by the membrane poison K. + and Na + pollute.

[0063] The basic compound is optimally metered into the feed so that the pH of the intermediate, measured at 25°C using a glass electrode, is between 9 and 12. In this pH window, the water splitting operates very well and the membrane is not attacked. The glass electrode used for determining the pH should be calibrated in a standard manner using defined test liquids.

[0064] The electrochemical cell may also be operated at temperatures other than 25° C. The pH should not be adjusted: the pH of the intermediate at the cell temperature should correspond to a pH of 9 to 12 at 25° C. The cell temperature may be from 20° C. to 70° C.

[0065] The addition of an alkaline compound has the additional advantage that undesirable ions present in the feed are bound. This protects the membrane and improves the purity of the product. More specifically, the addition of an alkaline compound makes it possible to process feeds containing one or more of the following anions: sulfate, carbonate, hydroxide, chloride and fluoride.

[0066] With this setup, it is possible for anions to be in equilibrium with the corresponding protonated ions in aqueous solution. The exact concentration depends on the exact pH of the corresponding solution and can be calculated with the help of the corresponding acid and base constants. The calculation is shown in:

[0067] Ruland(ed.)et al.:Analytik:Daten,Formeln, [Analytics:data,formulae,exercises],edition 109,2019,Walter de Gruyter GmbH&Co.KG pages257ff.

[0068] In addition to the anions mentioned, the feed may also contain impurities in the form of compounds of the following elements: B, Na, Mg, Al, Si, K, Ca, Mn, Fe, Co, Ni, Cu, C. The alkali metals and alkaline earth metals listed are elements found together with lithium in natural deposits, while the other metals mentioned are used as conductive or positive electrode materials in LIBs and are therefore present in the feed obtained from the reprocessing of used LIBs. The carbon originates from organic compounds present in the LIB, for example films, separators, sealants or adhesives.

[0069] According to the invention, a membrane comprising an inorganic material is used. Thus, the desired ion selectivity is achieved differently from the case of polymer membranes. The membrane preferably consists entirely of inorganic material. Composite membranes containing only inorganic material as a coating on a support material or dispersing inorganic material in different types of matrix materials have proven to be the wrong approach.

[0070] In order for this approach to work, the inorganic material must conduct Li ions and simultaneously act as an electrical insulator.

[0071] The specific conductivity σ for Li ions should be at least 1*10 at a temperature of 23°C. -5 S / m or at least 5*10 -5 S / m or at least 10*10 -5 S / m and not more than 100*10 -5 S / m. The Li conductivity of the material was measured by impedance spectroscopy. The measurement was performed as follows:

[0072] The measuring device consists of two cylindrical electrodes with the sample arranged between them. To ensure optimal contact with the electrodes and a reproducible contact pressure, a weight is placed on the sample.

[0073] A potentiostat (Zahner-Elektrik I. Zahner-Schiller GmbH & Co. KG, Kronach-Gundelsdorf, Germany) was connected to the electrodes and controlled via Thales software (Zahner). Measurements were performed in the frequency range of 1 Hz to 4 MHz and at an amplitude of 5 mV using samples that had been polished and sputtered on a thin conductive gold layer.

[0074] The measurement results are presented in the form of Nyquist plots and evaluated using analysis software (Zahner). The resistance is read at the maximum of the Nyquist plot curve. The formula σ = (h·10 4 ) / (R·π / 4·d 2 ) to calculate the specific ionic conductivity σ [mS / cm], where h is the sample height in mm, R is the measured resistance in Ω and d is the sample diameter in mm.

[0075] The specific conductivity γ (conductivity) of electrons should be less than 10 at 23°C. -7 S / cm(10 -9 S / m) or less than 10 -12 S / m or less than 10 -16 S / m. Therefore, from the perspective of electronic conduction, inorganic materials are classified as non-conductors.

[0076] LiSICon is preferably used as inorganic material. LiSICon material is a glass ceramic substance which conducts lithium ions and at the same time acts as an electrical insulator. For the purposes of the present invention, all known LiSICon materials can in principle be used as inorganic materials. Known LiSICon materials meet the requirements specified above for the electrical conductivity and ionic conductivity of inorganic materials.

[0077] For example, the LiSICon material lithium aluminum titanium phosphate (LATP) can be used. Thus, in one variant of the invention, the inorganic material is a compound with the following stoichiometry:

[0078] Li 1+x Al x Ti 2-x (PO4)3

[0079] Here, 0.1≤x≤0.3, wherein preferably x=0.3.

[0080] Alternatively, the LiSICon material lithium aluminium germanium phosphate (LAGP) may be used. Thus, in one variant of the invention, the inorganic material is a compound having the following stoichiometry:

[0081] Li 1+x Al x Ge 2-x (PO4)3

[0082] Where: x=0 or x=0.2 or x=0.4.

[0083] Alternatively, the material LiSICon lithium aluminum silicon titanium phosphate (LATSP) may be used. Thus, in one variant of the invention, the inorganic material is a compound having the following stoichiometry:

[0084] Li 1+x+y Al x Ti 2-x Si y P 3-y O 12

[0085] Where 0.1≤x≤0.3 and 0.2≤y≤0.4.

[0086] As an alternative to the phosphates mentioned, the oxidic LiSICon material lithium lanthanum titanium oxide (LLTO) can be used. Thus, in one variant of the invention, the inorganic material is a compound with the following stoichiometry:

[0087] Li 3x La (2 / 3)-x □ (1 / 3)-2x TiO3

[0088] Where 0≤x≤0.16.

[0089] However, particular preference is given to using LiSICon which is derived from lithium aluminium germanium phosphate but which additionally contains titanium. This is known as LAGTP.

[0090] Thus, in a preferred variant of the invention, the inorganic material is a compound having the following stoichiometry:

[0091] Li 1.4 Al 0.4 (Ge 1-x Ti x ) 1.6 (PO4)3

[0092] Where 0≤x≤1.

[0093] In a particularly preferred development of the invention, LATSP is used which additionally contains germanium. This is known as LAGTSP.

[0094] Thus, in a particularly preferred variant of the invention, the inorganic material is a compound having the following stoichiometry:

[0095] Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 *nGeO2

[0096] Where 0≤x≤1 and 0≤y≤1 and 0≤n≤1.

[0097] LAGTSP is available, for example, from OHARA GmbH, Hofheim, Germany under the product name AG01 obtained.

[0098] The lithium hydroxide is present in the rich working medium and is extracted from the second compartment together with the lithium hydroxide. In order to be able to utilize the lithium hydroxide, it needs to be separated from the rich working medium. A separation device is provided for this purpose. Therefore, a preferred development of the present invention comprises the following additional method steps:

[0099] m) providing separation equipment;

[0100] n) Separating the lithium hydroxide from the rich working medium with the aid of a separation device.

[0101] After the lithium hydroxide has been separated from the rich working medium, the working medium can be disposed of as wastewater or preferably reused as lean working medium. For this purpose, it is necessary to operate the separation device so that the LiOH is not completely separated, but maintained at a specified minimum concentration of 50 ppm LiOH c m0This allows the working medium to be recycled to the second compartment as lean working medium. This then results in recycling of the working medium between the second compartment and the separation device.

[0102] Therefore, a preferred development of the invention comprises the following additional method steps:

[0103] n) separating lithium hydroxide from the rich working medium by means of a separation device in order to obtain a lean working medium,

[0104] The steps

[0105] b) providing a lean working medium comprising water and lithium hydroxide dissolved therein, wherein the concentration of lithium hydroxide in the lean working medium is C based on the total weight of the lean working medium. M0 At least 50 ppm by weight;

[0106] With the help of separation equipment.

[0107] In order to make it possible to recirculate the working medium between the separation device and the second compartment, it makes sense to install both devices at the same location. The same location is to be understood as meaning an integrated production facility. The electrochemical cell and the separation device are therefore part of an integrated facility.

[0108] It is also conceivable that the separation device is located at a different location away from the electrochemical cell. In this case, however, the working medium must be transported between the cell and the separation device. However, from an energy point of view, this is of little significance.

[0109] Preferably, at least the electrochemical cell is operated continuously. This means that there is a constant throughflow between the two compartments. The first compartment has a continuous throughflow of the intermediate, resulting in the production of wastewater, while the second compartment has a throughflow of the working medium, which flows in as a lean working medium and flows out as a rich working medium. This makes it possible to have a higher throughput and to continuously extract the membrane-damaging components of the intermediate and the working medium. Therefore, it can be expected that continuous operation achieves better membrane stability than in batch operation.

[0110] An important aspect of this process is that the production of hydrogen and lithium hydroxide occurs simultaneously. This is accomplished by reacting Li + This is made possible by the combination of membrane electrolysis and electrochemical water splitting.

[0111] In the simplest case, the voltage applied to the electrochemical cell remains constant over time (DC voltage). However, it has been found to be advantageous to vary the voltage periodically over time. This is due to an increase in the service life of the membrane. One explanation for this could be that ions that damage the membrane are flushed away from the membrane when the cell is switched off.

[0112] In a preferred development of the method, the voltage drawn from the voltage source is varied periodically over time.

[0113] Preferably, the voltage changes in a waveform-like manner. Here, the waveform may be a sine wave, a square wave, a triangle wave or a sawtooth wave.

[0114] In the simplest case, the waveform is obtained by periodically changing the polarity of the voltage (AC voltage).

[0115] However, more preferably, the voltage is varied by switching it on and off periodically. When the voltage is on, a constant value is maintained. This produces a square wave. In this case, it can also be said that pulses of the voltage occur. It has been found to be advantageous when the period during which the voltage is on is longer than the period during which the voltage is off. Preferably, the period when on is 3 to 7 times longer than the period when off, preferably about 5 times longer.

[0116] Therefore, in a preferred development of the method, the waveform is a square wave, that is to say formed by a first band in which the voltage is switched on at a constant value and a second band after the first band in which the voltage is switched off, wherein the length of the first band is λ1 and the length of the second band is λ2, and the following relationship applies:

[0117] λ1=φ*λ2, where 3<φ<7.

[0118] With regard to the periodic variation of the voltage, it should also be noted that the voltage does not necessarily have to change polarity like an AC voltage. Although it is conceivable to allow the voltage to oscillate with an amplitude of about U=0, it is preferred to keep the polarity (i.e. the sign) of the voltage unchanged and only vary the amplitude of the voltage. Therefore, in a preferred development of the method, the polarity of the voltage is maintained.

[0119] The present invention will now be described in detail with reference to the process flow diagram. In the figure provided for this purpose:

[0120] Figure 1 :Simultaneous Li + Functional principles of membrane electrolysis and water electrolysis;

[0121] Figure 2 : Shows the functional principle of recycling between electrochemical cells and separation equipment.

[0122] The electrochemical cell 0 required to carry out the method is shown in Figure 1 It comprises a first compartment 1 and a second compartment 2. The two compartments 1 and 2 are separated from each other by a membrane 3. Arranged in the first compartment 1 is a negative electrode 4. Arranged in the second compartment 2 is a positive electrode 5. Therefore, the first compartment 1 can be called a negative electrode compartment and the second compartment 2 can be called a positive electrode compartment.

[0123] A first electrical lead 6 connects the negative electrode 4 to a voltage source 7. A second electrical lead 8 connects the positive electrode 5 to the voltage source 7. The selected polarity of the voltage source 7 is such that the positive electrode of the voltage source 7 is connected to the negative electrode 4 and the negative electrode of the voltage source 7 is connected to the positive electrode 5. This polarity is always maintained even if the amplitude of the voltage U drawn from the voltage source 7 changes over time. However, in the simplest case, U is constant over time.

[0124] The electric current I flows through the two electrical leads 6 and 8 and through the voltage source 7. Since the membrane 3 acts as an electrical insulator, there is no electrical short circuit between the two electrodes 4 and 5 through the membrane 3.

[0125] The membrane 3 is a flat plate membrane consisting entirely of LiSICon material. The negative electrode 4 is a metal flat plate containing titanium, niobium or tantalum. The positive electrode 5 is also a metal flat plate containing titanium or nickel. In the simplest case, a stainless steel plate is used as the positive electrode. The negative electrode 4, the positive electrode 5 and the membrane 3 have the same shape and can be rectangular or circular. Figure 1 This is not obvious from the side view of the electrode. Porous metal, mesh or net of a specified material may also be used as an electrode instead of a metal plate.

[0126] The electrochemical cell 0 has an effective area A corresponding to the surface areas of the membrane 3 , the negative electrode 4 and the positive electrode 5 .

[0127] During operation, the first compartment 1 is filled with an intermediate 9. The intermediate 9 is a Li + From an electrochemical point of view, intermediate 9 is regarded as the anolyte.

[0128] Intermediate 9 is obtained by mixing feed 10 with basic compound 11. Feed 10 can be a Li leaching solution from a natural ore deposit or a material stream generated by the reprocessing of used LIBs. Based on the total mass of the feed, the Li in feed 10 is + The concentration of cations (the formula symbol is c F ) should be at least 200 wt ppm. Seawater has a lower Li concentration and therefore must first be concentrated before it is used in the process. Feed 10 also contains anions, such as sulfate or chloride. Feed 10 also contains impurities. Anions and impurities are not shown in FIG. Figure 1 The main component of the feed 10 is water H2O. The pH of the feed is between 2 and 9.

[0129] The alkaline compound 11 is preferably calcium hydroxide Ca(OH)2 (slaked lime). The metering of the alkaline compound 11 into the feed 10 results in the formation of the intermediate 9. The purpose of adding the alkaline compound 11 to the feed 10 is to raise the pH to the alkaline range, more precisely to a pH between 9 and 13. According to the invention, the electrochemical process in the cell is carried out in an alkaline medium. The dosage of the alkaline compound 11 is selected accordingly so that a pH between 9 and 13 is reached in the intermediate. The intermediate 9 is fed into the first compartment 1.

[0130] The second compartment is filled with a lean working medium 12. The lean working medium 12 is a medium having a low concentration of C M0 Li + Cationic water H2O. Based on the total mass of the lean working medium 12, the concentration c M0 From an electrochemical point of view, the lean working medium 12 is considered to be a catholyte.

[0131] The electrochemical cell 0 is also charged with a voltage U drawn from the voltage source 7. This has the following effects:

[0132] First, water electrolysis occurs, where water (H2O) is electrochemically decomposed into hydrogen (H2) and oxygen (O2). At the positive electrode 5, OH - and hydrogen. However, OH - The anions cannot pass through the membrane 3 and interact with the Li + The cations combine to form lithium hydroxide (LiOH). At the negative electrode 4, oxygen and H + .

[0133] The Li from the intermediate 9 is driven by a voltage U + The cations migrate to the positive electrode 5 to maintain the formation of LiOH in the positive electrode compartment 2. They pass through the membrane 3 by virtue of the Li conductivity of the membrane and accumulate in the working medium (membrane electrolysis). This results in the formation of a rich working medium 13, which is withdrawn from the second compartment 2. The Li in the rich working medium 13 + The concentration of ions is greater than that of Li in the lean working medium 12 + The concentration of the ion, therefore c M1 >c M0 .

[0134] Therefore, water electrolysis, Li + The membrane electrolysis and LiOH synthesis are carried out simultaneously in the electrochemical cell 0.

[0135] In an electrochemical cell, Li +Membrane electrolysis and water electrolysis thus lead to the direct formation of lithium hydroxide LiOH and molecular hydrogen H2. LiOH dissolves in water, hydrogen partially dissolves in water and also exists in gaseous form. Water containing LiOH and dissolved hydrogen is withdrawn from the positive compartment of the cell as a rich working medium 13. Gaseous hydrogen is likewise withdrawn from the second compartment 2.

[0136] Due to membrane electrolysis, the Li + is exhausted, producing wastewater 14. Therefore, c W <c F Here, the formula symbol c W represents the concentration of Li ions in the wastewater 14 based on the total mass of the wastewater 14. Here, the formula symbol c F represents the concentration of Li ions in the feed 10 based on the total mass of the feed 10.

[0137] Figure 2 Depicts how LiOH is extracted as target product 15 from the rich working medium 13 .

[0138] For this purpose, a separation device 16 is provided, into which the rich working medium 13 is fed. The separation device 16 separates the target product 15 from the rich working medium 13 having a particularly high concentration of LiOH. The target product also contains water and impurities, depending on the desired specifications of the target product.

[0139] The separation device 16 may be a distillation column or a crystallizer.

[0140] The LiOH-depleted output stream from the separation device 16 is recycled as lean working medium 12 to the second compartment 2 of the electrochemical cell 0 .

[0141] As mentioned previously, the lean working medium 12 needs to have a certain LiOH concentration C M0 , so that the process in the electrochemical cell 0 can be started in the desired manner by virtue of the low initial resistance. Based on the total mass of the lean working medium 12, the concentration c M0 Should be at least 50 ppm by weight. To ensure the required concentration C M0 , the separation device 16 is operated so that not all of the LiOH is separated from the rich working medium 13.

[0142] In addition to lithium hydroxide LiOH, the process also produces H2. Hydrogen H2 is at least partially dissolved in the rich working medium 13 and is withdrawn from the second compartment 2 together with LiOH. Some hydrogen escapes from the second compartment 2 in the gaseous state.

[0143] Since hydrogen H2 is easily degassed from water, it can be removed from the rich working medium without much effort. Only when hydrogen H2 is used as a second target product is a corresponding second separation device provided, with which hydrogen (not depicted) is obtained separately with appropriate quality / purity.

[0144] The water H2O present in the rich working medium 13 is recycled as completely as possible as the lean working medium 12. Only the water present in the target product 15 is lost from the process. This must be replenished in the lean working medium 12 as required (not depicted). The water in the intermediate 9 originating from the feed is not finally recycled between the second compartment 2 and the separation device 16, because the membrane 3 is impermeable to water. Example

[0145] Experimental setup and procedure

[0146] The following description is intended to describe the effects of impurities in the form of foreign ions on the ceramic lithium conducting membrane during electrolysis. The effects of pH and voltage cycling are also described.

[0147] To carry out the electrolysis, the electrolysis cell is first assembled and the anolyte and catholyte containers are connected. Care must be taken here to ensure that the inflow and return are connected in each case on the same side.

[0148] The negative and positive electrodes used were in each case discs with a diameter of 19.5 mm and a thickness of 1 mm. The material was in each case a titanium porous metal sheet coated on both sides with IrTi mixed oxide, 12 g Ir / m2, 1AF D 1.5 mm, from Metakem GmbH, 61250 Usingen, Germany.

[0149] The sampled membranes were likewise disks with a diameter of about 25 mm. The membrane thickness was about 1 mm. The materials of the sampled membranes are specified in the individual examples.

[0150] The electrolysis vessel and the corresponding reservoir container were blanketed with nitrogen throughout the duration of the process to prevent the formation of lithium carbonate. Each cell had a separate anolyte container and a separate catholyte container. Each container was filled with about 1 kg of liquid; the exact mass was determined by reweighing. In all experiments, the catholyte was always a 5 mmol / L LiOH solution (corresponding to 120 wt ppm LiOH). In each case, the anolyte was a lithium salt solution at different concentrations and with various lithium salts.

[0151] The experiment begins after the pump is started and the required voltage is applied. The maximum flow rate is 900 mL / min. Samples are collected every half hour, or at longer time intervals if an agreement has been reached. The first 3 mL of sample collected are discarded. For each sample collected, the power in each case is recorded and the pH and conductivity of the sample are determined. The sample is then returned to an appropriate container to keep the volume almost constant.

[0152] At the end of the experiment, the container was emptied and all leads as well as the membrane were rinsed with demineralized water. The cell was disassembled, the membrane was photographed and SEM images of the catholyte and anolyte sides were recorded to document any damage or changes to the membrane.

[0153] Some experiments with adjustment of the anolyte pH were performed to confirm the hypothesis that low pH has an adverse effect on membrane performance. Experiments without adjustment of the pH gave very poor results. In experiments with adjustment of the pH, the pH of the anolyte solution was adjusted to the desired range before the start of the experiment by appropriate metered addition of alkaline compounds. If the pH dropped during the experiment, further base was metered in to maintain the pH. In contrast to this were experiments in which the pH dropped during the electrolysis according to the natural properties of the solution.

[0154] In experiments using voltage pulses, the voltage supply is interrupted for a defined time interval so that no voltage is applied to the electrochemical cell during this time. The voltage is run as a square waveform with no polarity change over time. The purpose is to flush the membrane free of potentially interfering ions (H+) during the no-voltage time to reduce damage to the membrane and improve membrane performance.

[0155] Membrane performance is measured by parameter permeability (g Li*mm / m 2 *h) and permeance (gLi / m 2 *h). Permeability indicates how much mass of lithium is transported through the membrane per unit membrane area and per unit time. Permeability also takes into account membrane thickness and therefore also makes it possible to compare different membrane types with different thicknesses. To fully describe the performance, both are needed, because very thin membranes will allow very high permeabilities, but if there are concentration polarization effects in the membrane cell, the permeability will give an inaccurate picture. Taking membrane thickness into account will no longer serve any useful purpose, because the transport is not limited by the membrane.

[0156] All measurements shown in the examples are subject to a measurement error of approximately ±10% which is attributable to the positioning of the electrodes relative to each other, the determination of the film sample thickness and inaccuracies in the concentration determination via conductivity measurements.

[0157] All ceramics used were sourced from the manufacturers listed in Table 0 and can be ordered from these sources under the corresponding product names.

[0158] Table 0: Ceramics used and their manufacturers

[0159]

[0160] The lithium hydroxide used was analytical grade from Aldrich. All other materials used were technical grade.

[0161] Unless otherwise stated, LATSP films with a thickness of approximately 1 mm were used ( Ohara). The membrane disk is sintered by SPS process at 100*10 5 Pa to 200*10 5 Pa pressure and 950°C temperature or obtained directly from the respective manufacturers (Ohara, Ampcera, Toshima) in appropriate dimensions for measuring cells.

[0162] Description of the sintering process

[0163] Sintering by FAST / SPS

[0164] The LATSP powder used is sintered by FAST / SPS (field assisted sintering technology / spark plasma sintering). The sintering is carried out under the condition of increasing pressure and temperature at the same time to achieve high compaction and effective sintering in a very short sintering time. The sintering mold assembly consists of a graphite mold with an outer diameter of 80mm, an inner diameter of 36mm and a height of 55mm, two graphite half shells with a wall thickness of 10mm and the same height, and two graphite punches with a diameter of 25mm and a height of 30mm. The half shell is placed in the mold and a punch is introduced into the half shell from below. Before 2.5g of powder is weighed onto the lower punch in the mold, a graphite foil is placed on the punch to obtain better contact. After weighing the powder, a second graphite foil is placed on the powder and an upper punch is introduced into the half shell. The mold assembly is placed between two plates in the furnace chamber of the FAST / SPS furnace, each of which is made of carbon fiber reinforced graphite. The assembly is contacted and the required pressure is established via the path of travel of the electrode. The mold is additionally heated by alternating current, which allows high temperatures to be reached in a short time. After gradually increasing the temperature to 250°C over five minutes, heating is continued at a rate of 130°C / min until a maximum temperature of 900°C is reached, which is maintained for a further five minutes. During the temperature increase, the pressure is also increased to 43 MPa for five minutes, which is also maintained for five minutes. At the end of the holding time, the contact of the upper electrode is released from the mold and the mold cools down. The sintered film can then be removed from the mold.

[0165] Example 1 (LATSP)

[0166] First, the voltage dependence of the ceramic membrane during electrolysis was studied. Electrolysis was performed with 0.1 mol / L LiOH and 1 mol / L LiOH at voltages ranging from 3 V to 6 V. The measurement results are shown in Table 1.

[0167] In the graph of the values, the linear relationship is clear. The point where the line intersects the x-axis at about 2V is derived from the decomposition voltage of water and the internal resistance of the cell. This intersection point is almost the same for both concentrations. The graph is shown in Figure 3 middle.

[0168] Table 1: Voltage dependence of electrolysis with ceramic membranes

[0169]

[0170] Example 2 (LATSP)

[0171] It was also determined that the membrane performance was independent of the anolyte concentration. For this purpose, electrolysis was performed at voltages of 3 V and 6 V, in each case with an initial charge of 0.1 mol / L, 1.0 mol / L, 2.0 mol / L or 4.0 mol / L LiOH, respectively, in the anolyte container.

[0172] The molar proportion of LiOH corresponds to the following weight proportion of Li:

[0173] 0.1mol / L=700ppm Li=2400ppm LiOH

[0174] 1.0mol / L=7000ppm Li=24000ppm LiOH

[0175] 2.0mol / L=14 000ppm Li=48 000ppm LiOH

[0176] 4.0mol / L=28 000ppm Li=96 000ppm LiOH

[0177] The measurement results are shown in Table 2. At concentrations of 1 mol / L to 4 mol / L, no significant increase in membrane performance was measured. A LiOH concentration of 0.1 mol / L achieved slightly lower performance. Figure 4 The results in graphical form are shown.

[0178] Table 2: No dependence on anolyte concentration

[0179]

[0180] Example 3 (LATSP)

[0181] Electrolysis was performed at 3 V, 4 V and 6 V, using in each case the appropriate lithium salt at 0.1 mol / L lithium in the recirculating anolyte. At the start of the experiment, after a short run time (shown in parentheses), the permeabilities were of similar order of magnitude. In the case of lithium hydroxide and lithium carbonate, the permeabilities increased as expected by the higher voltages, while in the case of lithium chloride and lithium sulfate, the permeabilities decreased after longer runs at higher voltages.

[0182] pH measurements at the end of each experiment showed that the pH of the lithium chloride and lithium sulfate solutions had dropped to pH 3-4.

[0183] The measured values ​​are shown in Table 3. Figure 5 The results in graphical form are shown.

[0184] Table 3: Effect of anions on permeability

[0185]

[0186] Example 4 (LATSP)

[0187] In order to more closely examine the effect of the pH of the recirculating anolyte on membrane performance during electrolysis, comparisons were made using lithium chloride at concentrations of 0.1 mol / L and 1.0 mol / L at pH 4 and 11 and at an electrolysis voltage of 3 V. The pH was adjusted with a few drops of 1.0 mol / L lithium hydroxide solution. For both concentrations, increasing the pH achieved an increase in permeability. When electrolysis was performed using a LiCl solution that was not adjusted in pH with lithium hydroxide, the anolyte pH steadily decreased, so the permeability in these measurements was subject to error when it was related to pH because the pH could not remain constant for a long time.

[0188] The results are reported in Table 4. Figure 6 The results in graphical form are shown.

[0189] Table 4: Effect of pH on permeability / / adjusted with LiOH

[0190]

[0191] Example 5

[0192] The effect of pH of the recirculating anolyte was tested using a 1.0 mol / L LiCl solution in a 24 hour experiment where the voltage was increased.

[0193] Low pH and increasing voltage (3 to 8 V) did not keep the permeability stable. During the experiment, the pH varied depending on the run time until it stabilized at approximately pH 4, which means that the permeability also did not reach a constant value during the experimental time.

[0194] When the pH was adjusted by adding a small amount of LiOH solution, the permeability stabilized at a high level. The results are collated in Table 5 after about 3 to 5 hours of stabilization. Figure 7 The results in graphical form are shown.

[0195] Table 5: Dependence of permeability on pH and voltage

[0196]

[0197] Example 6 (LATSP)

[0198] Since pH adjustment with lithium hydroxide is not yet feasible, the pH of the recirculating anolyte was adjusted with (Ca(OH)2) in this experiment. The poor solubility of calcium hydroxide makes it difficult to meter in further amounts when the pH drops: the intermediate contains a certain proportion of solid matter and is slightly turbid. The experiments were carried out using a 0.1 mol / L lithium chloride solution that had been adjusted to pH 12 with Ca(OH)2.

[0199] Adjusting the pH with Ca(OH)2 resulted in a significant increase in membrane permeability of more than 50%. The results are summarized in Table 6. Figure 8 The results in graphical form are shown.

[0200] Table 6: Effect of pH on permeability / / Adjusted with Ca(OH)2

[0201]

[0202] Example 7 (LATSP)

[0203] Likewise, when lithium sulfate Li2SO4 is the salt in the recycled anolyte, it is accompanied by a pH drop and membrane damage during electrolysis. In this case, adjusting the pH with Ca(OH)2 does not lead to improved membrane performance because of the formation of poorly soluble CaSO4 that precipitates on the membrane. Adjusting the pH with a 1.0 mol / L LiOH solution does not lead to the formation of deposits on the membrane or a sharp drop in permeability, but improves them. The results are reported in Table 7. Fig. 9 The results in graphical form are shown.

[0204] Table 7: Effect of Li2SO4 on permeability

[0205]

[0206] Example 8 (LATSP)

[0207] Lithium carbonate behaves differently than lithium chloride and lithium sulfate as the salt in the anolyte. The membrane performance at 4 V is slightly lower than that at 6 V. Between 8 V and 10 V, the permeability fluctuates, reaching a plateau such that increasing the voltage does not result in an increase in permeability.

[0208] This can be attributed to the limited solubility of lithium carbonate, which allows a maximum concentration of only about 0.15 mol / L. As already described in Example 2, the permeability at lower lithium concentrations is lower. In addition, due to the buffering effect of Li2CO3, it is only possible to a limited extent to increase the pH by adding Ca(OH)2. Overall, this is the reason why Li2CO3 behaves differently in the electrolysis experiments compared to LiCl and Li2SO4. The results are recorded in Table 8.

[0209] Table 8: Effect of adding Ca(OH)2 on permeability when using LiCl, Li2SO4 and Li2CO3

[0210]

[0211] Example 9 (LATSP)

[0212] To minimize the loss of permeability due to the addition of the Ca(OH)2 solution, experiments were performed with additional voltage pulses. Two different pulse intervals were tested. For pulse interval 1, the voltage was on for 10 seconds and then off for 2 seconds. This achieved a 25% increase in permeability.

[0213] For pulse interval 2, the voltage was on for 50 seconds and off for 10 seconds, and a 61% permeability increase was achieved.

[0214] Table 9 compares a series of experiments using lithium chloride, each with a different pulse interval 1 and 2 and an arrangement of pH adjustment with LiOH and Ca(OH)2. The reference values ​​are comparative values ​​for lithium hydroxide. The best performance here was achieved with lithium chloride and Ca(OH)2 and a pulse interval of 2. All experiments were run with 0.1 mol / L LiCl, 6V and a cross flow rate of 900 ml / min. The results are shown in Table 9 and are presented graphically in Fig.10 middle.

[0215] Table 9: Effect of pulse voltage and interaction with added Ca(OH)2

[0216]

[0217] Example 10 (Testing of various LiSICon materials)

[0218] Various LiSICon materials for use in an electrochemical process for producing lithium hydroxide and hydrogen are described by measuring the permeability of an alkaline 1.0 mol / L lithium hydroxide solution as the anolyte at different voltages. The results are shown in Fig.11 middle.

[0219] This gives a good idea of ​​the material's properties, but it should also be noted that materials with lower permeabilities can be effectively used in this process if they are processed into thin films.

[0220] The materials studied are listed in Table 0. Fig.11 and 12 In the keywords, LATSP stands for PW01, LATSP-AG-01 stands for AG01, LATSP-SP01 representatives SP-01, both from Ohara. LAGP stands for Ampcera material and LLTO stands for Toshima material.

[0221] Alternatively, the behavior of different ceramics can also be described by their permeability in the respective case ( Fig.12 ). This representation is more appropriate when mass transfer in the electrolysis cell is limited. The reason why LATSP SP01 differs from the other LiSICon studied in this representation is probably because this material, with a thickness of 0.15 mm, is very thin and therefore not as stable as the other materials studied.

[0222] Fig.11 and 12 The underlying measurements are shown in Table 13.

[0223] Table 13: Measured values ​​of Example 10

[0224]

[0225] Example 11 (LAGP)

[0226] The alkaline anolyte solution was spiked with approximately 1000 ppm (g / g) of each of the following cations: sodium; potassium; magnesium; calcium. LAGP membranes from Ampcera were used to transfer lithium from the solution to the catholyte, with permeabilities collated at Fig.13 Ion exchange chromatography analysis showed that all catholytes (purified LiOH) contained less than 10 ppm of the corresponding impurities. In each run, a 5 V voltage pulse with a pulse interval of T2 as described in Example 9 was used.

[0227] Example 12 (LATSP)

[0228] The alkaline anolyte solution was spiked with approximately 1000 ppm of sodium ions. A LATSP membrane (LICGC PW01, Ohara, sintered as described above) was used to enrich the catholyte with lithium from the solution, the permeability is shown in Fig.14The permeability in the absence of Na is shown as a comparison. The cell voltage was 5 V and pulses were performed with a pulse interval of T2 as described in Example 9. Ion exchange chromatography analysis showed that the purified LiOH contained less than 10 ppm of sodium ions.

[0229] Ion chromatography analysis

[0230] In Examples 11 and 12, the content of Li and Na ions in the analyte and the cathode solution was determined by ion exchange chromatography (IEC) as follows:

[0231] Before measurement, the sample was filtered through a syringe filter ( Xtra MV-20 / 25, pore size 0.20μm, for filtration of aqueous and polar media.

[0232] Prior to the study, the IEC instrument (Metrohm IC 930 Compact, C Supp C6 250 / 4.0, standards (1.7 mM HNO3, 1.7 mM dipicolinic acid), conductivity sensor) was referenced and externally calibrated for Li and Na. The calibration lines used are shown in Fig.15 (for Na) and Fig.16 (For Li)

[0233] in conclusion

[0234] The experiments showed that the presence of lithium sulfate, lithium chloride and lithium carbonate worsened the permeability of the studied membranes. However, by adding hydroxides, such as Ca(OH)2 and LiOH, the detrimental effects could be reversed, especially when the voltage was pulsed. High permeability is a prerequisite for high process efficiency. Therefore, the measures discovered help the process to run more efficiently.

[0235] Reference Numbers List:

[0236] 0 Electrochemical Cell

[0237] 1 First compartment

[0238] 2 Second compartment

[0239] 3 Membrane

[0240] 4 Anode

[0241] 5 Cathode

[0242] 6 First electrical lead

[0243] 7 Voltage Source

[0244] 8 Second electrical lead

[0245] 9 Intermediates

[0246] 10 Feed

[0247] 11 Basic compounds

[0248] 12 Lean working medium

[0249] 13 Rich working medium

[0250] 14 Wastewater

[0251] 15 Target product

[0252] 16 Separation equipment

[0253] H2O water

[0254] H2 Hydrogen

[0255] O2 Oxygen

[0256] LiOH Lithium Hydroxide

[0257] OH - OH anion

[0258] Li + Lithium cation

[0259] U Voltage

[0260] I Current

[0261] A Effective area

[0262] C F LiOH concentration in feed

[0263] C W LiOH concentration in wastewater

[0264] C M0 LiOH concentration in lean working medium

[0265] C M1 LiOH concentration in rich working medium

Claims

1. A method for producing hydrogen and lithium hydroxide, comprising the following steps: a) providing a feed comprising at least water, Li cations, anions and impurities, wherein the concentration of Li cations in the feed is C F at least 200 ppm by weight or between 500 ppm by weight and 140 000 ppm by weight, in each case based on the total weight of the feed, the pH of the feed being between 2 and 9, measured at 25° C. using a glass electrode; b) providing a lean working medium comprising water and lithium hydroxide dissolved therein, wherein the concentration of lithium hydroxide in the lean working medium is C based on the total weight of the lean working medium. M0 At least 50 ppm by weight; c) providing a basic compound; d) providing at least one electrochemical cell, wherein the electrochemical cell has the following properties: i. The electrochemical cell comprises a first compartment in which a negative electrode is arranged; ii. The electrochemical cell comprises a second compartment in which a positive electrode is arranged; iii. The electrochemical cell comprises a membrane separating the first membrane from the second membrane, the membrane having an area A; iv. The membrane comprises an inorganic material having conductivity to Li ions and electrical insulation; e) providing at least one voltage source connected to the negative electrode via a first electrical lead and to the positive electrode via a second electrical lead; f) metering the basic compound into the feed so that an intermediate is obtained, the pH of which, measured at 25° C. using a glass electrode, is between 9 and 13; g) filling the first compartment with the intermediate; h) filling the second compartment with the lean working medium; i) charging the electrochemical cell with a voltage U drawn from the voltage source so that a current I flows between the negative electrode and the positive electrode, the ratio Q of the current intensity of the current I to the area A of the membrane being between 100 A / m 2 and 500A / m 2 Between or 150A / m 2 and 350A / m 2 between; j) extracting wastewater containing at least water, Li salt dissolved therein, oxygen and impurities from the first compartment, wherein the concentration of Li ions in the wastewater is C based on the total weight of the wastewater. W Lower than the concentration of Li ions in the feed C F ; k) extracting a rich working medium containing water, lithium hydroxide and hydrogen from the second compartment, wherein the concentration of lithium hydroxide in the rich working medium is C based on the total weight of the rich working medium. M1 Greater than the concentration C of lithium hydroxide in the lean working medium M0 .

2. The method according to claim 1, characterized in that The alkaline compound is selected from Ca(OH)2, KOH, NaOH, LiOH and NH4OH.

3. The method according to claim 2, characterized in that The alkaline compound is Ca(OH)2.

4. The method according to claim 1, 2 or 3, characterized in that: The pH of the intermediate was between 9 and 12 measured at 25°C using a glass electrode.

5. The method according to any one of claims 1 to 4, characterized in that The anions present in the feed are selected from sulfate, carbonate, hydroxide, chloride and fluoride.

6. The method according to any one of claims 1 to 5, characterized in that The feed contains impurities in the form of compounds of elements selected from the group consisting of B, Na, Mg, Al, Si, K, Ca, Mn, Fe, Co, Ni, Cu and C.

7. A method according to any one of the preceding claims, wherein the inorganic material present in the membrane has a specific conductivity σ for Li ions, measured by the "Impedance Spectroscopy" method described herein, of at least 1*10 -5 S / m or at least 5*10 -5 S / m or at least 10*10 -5 S / m and not more than 100*10 -5 S / m.

8. The method according to claim 7, characterized in that The inorganic material is a compound with the following stoichiometry (LATP): Li 1+x Al x Ti 2-x (PO4)3 Here, 0.1≤x≤0.3, wherein preferably x=0.

3.

9. The method according to claim 7, characterized in that: The inorganic material is a compound with the following stoichiometry (LATSP): There 1+x+y To the x You 2-x Yes y P 3-y OR 12 Where 0.1≤x≤0.3 and 0.2≤y≤0.

4.

10. The method according to claim 7, characterized in that The inorganic material is a compound with the following stoichiometry (LAGTSP): The 1+x+y Al x Ti 2-x If y P 3-y O 12 *nGeO2 Where 0≤x≤1 and 0≤y≤1 and 0≤n≤1.

11. The method according to claim 7, characterized in that The inorganic material is a compound with the following stoichiometry (LAGTP): Li 1.4 Al 0.4 (Ge 1-x Ti x ) 1.6 (PO4)3 Where 0≤x≤1.

12. The method according to claim 7, characterized in that The inorganic material is a compound (LAGP) having the following stoichiometry: <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> 1+x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> Ge<h2 style=";text-align:left;direction:ltr"> 2-x <h2 style=";text-align:left;direction:ltr"> (PO4)3 Where: x=0 or x=0.2 or x=0.

4.

13. The method according to claim 7, characterized in that The inorganic material is a compound having the following stoichiometry (LLTO): He 3x The (2 / 3)-x □ (1 / 3)-2x TiO3 Where 0≤x≤0.

16.

14. The method according to any one of the preceding claims, comprising the additional step of: m) providing separation equipment; n) separating the lithium hydroxide from the rich working medium by means of the separation device.

15. The method according to claim 14, characterized in that The steps n) separating the lithium hydroxide from the rich working medium by means of the separation device; Obtaining the lean working medium, Make the steps b) providing a lean working medium comprising water and lithium hydroxide dissolved therein, wherein the concentration of lithium hydroxide in the lean working medium is C based on the total weight of the lean working medium. M0 At least 50 ppm by weight; This is carried out with the aid of the separation device.

16. The method according to claim 14 or 15, characterized in that The electrochemical cell and the separation device are arranged at the same location.

17. The method according to any one of claims 1 to 16, characterized in that At least the electrochemical cell operates continuously.

18. The method according to any one of claims 1 to 17, characterized in that The production of hydrogen and lithium hydroxide takes place simultaneously.

19. The method according to any one of claims 1 to 18, characterized in that The voltage drawn from the voltage source varies periodically over time.

20. The method according to claim 19, characterized in that The voltage drawn from the voltage source varies over time in a waveform-like manner, the waveform being selected from the following waveforms: a sine wave, a square wave, a triangle wave, or a sawtooth wave.

21. The method of claim 20, wherein the waveform is a square wave, that is, formed by a first band in which the voltage is turned on at a constant value and a second band in which the voltage is turned off after the first band, wherein the length of the first band is λ1, the length of the second band is λ2, and the following relationship applies: λ1=φ*λ2, where 3<φ<7.

22. The method according to claim 19, 20 or 21, characterized in that The polarity of the voltage is maintained.

23. The method according to any one of claims 1 to 22, characterized in that The prevailing pH in the first compartment and in the second compartment was between 9 and 13 measured at 25°C using a glass electrode.

Citation Information

Patent Citations

  • Method for preparing lithium hydroxide through electrolysis of salt lake brine

    CN103924258A

  • Method for preparing lithium hydroxide from lithium-containing low-magnesium brine

    CN111394745A

  • Device and method for recovery or extraction of lithium

    US20120103826A1

  • Processes for preparing lithium hydroxide

    US20160032471A1

  • Processes and systems for preparing lithium hydroxide

    US20160258071A1